Career Development and Work Motivation Towards Organizational Commitment and Employee Performance - Rahma Nurdiana (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to examine the effect of career development and work motivation on organizational commitment and employee performance at the Procurement of the Goods/Services Administration Bureau of the Regional Secretariat of Central Java Province. Methodology/Approach: This study employed a quantitative approach with a causal research design. The population consisted of 90 APBJ employees, using a saturated sampling technique. Data were collected through questionnaires using Google Forms and analyzed with Partial Least Squares (PLS) using SmartPLS software. Results/Findings: The findings indicate that career development and work motivation have a positive and significant impact on organizational commitment and employee performance. Additionally, organizational commitment mediates the relationship between career development and work motivation and employee performance. Conclusions: This study concludes that both career development and work motivation play crucial roles in enhancing employee performance, primarily by strengthening organizational commitment. Limitations: This study is limited to APBJ Setda Central Java employees in 2024 and focuses only on career development and work motivation as independent variables, organizational commitment as an intervening variable, and employee performance as the dependent variable. Contributions: This study provides practical insights for APBJ leaders to enhance employee performance through effective career development programs and motivation strategies while strengthening organizational commitment. Theoretically, it enriches the human resource management literature in the context of public sector organizations.